(untitled) (Journal of Small Business Strategy (archive only), 1999)
Geographic Information Systems (GIS) are a specialized type of computer information system that allows users to display a wide range of data on a map. The increasing availability of demographic and other information in computerized form has lead to an expansion of the use of GIS into the business world. The increasing power of relatively inexpensive personal computers, improvements in user interfaces for GIS, and falling prices for an increasingly diverse range of GIS data products have all contributed to a situation where small businesses can take advantage of capabilities that were previously the exclusive domain of the large corporation. This article provides an introduction to GIS capabilities for the small business end-user and provides information to aid the reader in deciding whether GIS may be applicable to their business decision making needs.